Risk Factors Assessment for Intermodal Transport of Frozen Cargo - Ludmila FILINA-DAWIDOWICZ; Piotr TROJANOWSKI; Sara STANKIEWICZ (Communications of International Proceedings, 2021)
Intermodal transport of food perishable cargo is associated with a risk that may lead to these cargoes quality loss. The aim of the article is to analyze the risk factors associated with intermodal transport of frozen cargoes in refrigerated containers. The article considers a case study and examines the opinions of forwarders operating in Poland on the risk factors occurring during intermodal transport of frozen cargoes. The article identifies risk factors that may occur during the transport of refrigerated containers. Marketing research was used to collect information, which was analyzed in detail. The qualitative method was applied to assess the risk factors influence. It was found that according to the surveyed forwarders opinion, the failure of refrigeration unit of the container and cargo theft are the most severe risk factors appeared during frozen cargoes intermodal transport. The results of the research may be of interest to forwarders, transport companies and other entities involved in transport of perishable food products, including frozen ones.
Keywords: Intermodal Transport; Frozen Cargo; Risk Factors; Marketing Research; Refrigerated Container.